Puncture vine (Tribulus Terrestris L.) in control of health and reproduction - Sirotkin, Alexander V; Kolesárová, Adriana (Physiological research, 2021)
Tribulus terrestris, L. (puncture vine) have been used as a folk medicine for five thousands of years, but its targets, effects, their mechanisms and application requires further studies. This paper reviews the provenance, constituents and properties of Tribulus terrestris, L., its general physiological and health effects, as well as the currently available knowledge concerning its influence on male and female reproductive processes and their dysfunctions. Analysis of the available publications demonstrated the influence of Tribulus terrestris on a wide spectrum of targets and physiological processe and disorders. In particular, Tribulus terrestris can be a stimulator of male and female reproductive processes at the level of central nervous system, sexual behaviour, pituitary and gonadal hormones and their receptors, gonadal functions (including ovarian follicullogenesis and spermatogenesis), improvement of the quality and quantity of gametes (at least of sperm) and fecundity. This ability of puncture vine is applicable for the improvement of man's sexual desire and sperm quality in vivo and in vitro, as well as of women's libido, activation of women's reproductive organs, fecundity, and treatment of infertility, especially that related to the polycystic ovarian syndrome.
Keywords: Plant Extracts; rostlinné extrakty; Reproduction; libido; sexuální chování; rozmnožování; Tribulus; lidé; Female; Libido; mužské pohlaví; Male; ženské pohlaví; Sexual Behavior; Humans